Academic Business: Suan Dusit University - Polpuntin, Siroj; Chaleysub, Sukum; Tammasaeng , Maliwan; Udomtamanupab, Siratam; Tungdamnernsawad, Supaporn (Suan Dusit Graduate School Academic Journal, 2024)
This article describes academic business. A case study of Suan Dusit University. Starting with the development of laws and practices, management's perspective on thinking and doing, university philosophy, academic business development concepts, business concepts of Suan Dusit University, and academic wealth and direction of development of Suan Dusit University. Academic business comes from the word business; means that entrepreneurship aimed at trading for profit, and the word academic; means that subject of knowledge in one or more fields. “Academic business” in this article means creating new knowledge from the academic base where the university has expertise and putting innovation into practice for the benefit of teaching, training, research, community service, and business continuity of Suan Dusit University.